PENGARUH PERKEMBANGAN INDUSTRI MANUFAKTUR TERHADAP PERTUMBUHAN EKONOMI di INDONESIA - Mohamad Faisal; Reza Hermawan; Aprilliantoni, Aprilliantoni (Cahaya Ilmu Bangsa, 2024)
In Indonesia, the manufacturing industry sectorisa sector that is experiencing very rapid development. The manufacturing industry sector is very important for a country's economic development because of its contribution national economic development goals, especially in the formation of a large GDP and its ability to increase high added value. This study was conducted by describing facts, situation sorcircum stances. The data collected is secondary data, obtained from literature, journals, new spapers, and the Central Bureau of Statistics (BPS). The results ofthis study are that the development of the manufacturing industry in Indonesia has increased continuously over the last 5 years. Even though all countries were hitby the Covid-19 pandemic, the government quickly adopted policies to continue to improve economic development in Indonesia. Even though it is experiencing a pandemic condition, Indonesia's economic conditionis said to be quite good. This is evidenced that in November 2019 Indonesia was in third place inthe G20. Then in 2020 BankWord predicts that Indonesia's economic development will still be atac on traction rate of-2.2% and the realization will reach 2.07%. In 2021 the World Bank predicts Indonesia's development in the economic sector will reach 4.4% higher than Japan, Thailandand America.